Investigating the effects of financial instability on macroeconomic variables with time-varying vector autoregression (TVP-VAR) - fatemehsadat mohammadifard; Mohsen Mehrara; Sajad Barkhordari (اقتصاد باثبات)
Financial instability refers to a situation in which the economy has suffered losses and problems under the influence of asset price fluctuations or the poor performance of financial institutions in fulfilling their obligations. Fluctuations in asset prices and performance in the country's financial markets have led to the spread of instability and this has shown the weak financial depth in the country's financial markets. Based on this, the main goal of this paper was to investigate the effects of financial instability on macroeconomic variables in Iran. For this purpose, the statistical information of the period 1983-2022 has been used based on the frequency of annual data. In order to model the effects of financial instability on macroeconomic variables, the time-varying parameters vector autoregression (TVP-VAR) was used. The financial instability shock was extracted and calculated through the measure of financial conditions based on the combination of interest rate, inflation rate and exchange rate, and was modeled with the autoregressive conditional heteroskedasticity. In this study, results determined that there is a correlation between financial instability and macroeconomic variables. The results showed that the shock caused by financial instability led to an increase in the interest rate, inflation rate, exchange rate and liquidity growth and also led to a decrease in the growth of consumption, investment and GDP. According to the obtained results, it can be stated that financial instability has caused instability in economic growth by creating inefficiency in the allocation of resources and non-optimal allocation of resources and disrupting the movement of financial resources from savers to investors. As a result, it causes disturbances in macroeconomic variables.